Conflitos de deveres e dilemas morais: uma problematização a partir da teoria moral de I. KANT - Nunes, Lauren de Lacerda (2010)
The present work aims to problematize the question of the moral conflicts or conflict of duties in the Kantian ethical theory and in the post contemporary contribution for the referred discussion. In a first moment, the concept of moral conflict per se is characterized, i.e., out of the sphere of the Kantian theory, in order to comprehend the intrinsic relevance of this theme. Through this characterization it s demonstrated that the mere affirmation of the moral conflicts is capable to incite important consequences in normative moral theory and in metaethics, and that the Kantian s denyal of moral conflicts deserves to be studied more deeply. So, in a second moment the Kantian moral theory is properly approached. The Kantian approach of the conflict of duties is demonstrated through the exposition of the passage of the Metaphysics of Morals, in which Kant mentions that a collision of duties is inconceivable . The searching for the clarification of this denyal is done through the exploration of another Kantian works, like Critique of Pure Reason, Groundwork of the Metaphysic of Morals and Critique of Pratical Reason. Beyond that, the contemporary voices in the debate are also used in order to establish the Kantian argument. Authors like McConnell, Brink, Donagan and others, were also concerned with the denyal of moral conflicts, and through their help it s possible to glimpse what could be the whole Kantian argument against the moral conflicts. It s also showed that this argument is mainly based on two metaethical principles: the Kantian Principle and the Aglomeration Principle. An analysis of these principles is done too. The theories that vindicate the existence and authenticity of the moral conflicts are approached in a third moment. These theories started working with the affective remainders or gaps (regret, guilt or remorse). Authors that developed these ideas are Williams and Marcus. Gowans carries out the defense of the conflicts in supporting the idea of the inescapable moral wrongdoing, in which it s postulated that whatever the choice is made by an agent in some conflicts, he will do something wrong, no matter what. And that he will regret or fell moral distress after the decision. Gowans also vindicates a theory called Responsibilities to Persons Account made with the objective of accommodating the idea of this inescapable moral wrongdoing in moral conflicts. The theory of Gowans has proved to be effective in dealing with these questions, although it lacks objectivity, because it focuses on just some cases of conflicts. The Kantian answer to this problem (of the inescapable moral wrongdoing)is also explored in the end of this work. That answer will be based mainly on the idea of the superiority of the moral law before the particular person and in the formula of the humanity as an end in itself. However, the answer reveals the difficulties that the Kantian moral theory met in dealing with the moral conflicts that involve agent s responsibilities with intimates.